Studying Genealogy as a Factor of Cultural Self-Identification of the Person - M. E. Kudryavtseva (Дискурс)
Introduction. The paper considers the problem of cultural identity influenced by the study of ancestry. The scientific novelty of this paper is due to the attention to the psychological aspects of self-identity under the influence of the study of person, her or his ancestry, and, above all, in a situation of detection of undesirable information about his or her family's past. It is hypothesized that motifs associated with the need to rethink its social role in terms of responsibility for the acts of their ancestors, do not play a significant role in the study of family history.Methodology and sources. The paper analyzes the results of the pilot Internet study conducted to determine the motives and methods of the study of person's ancestry, as well as the stability of interest in this activity. The target audience of this study were all who are interested in learning their ancestors, regardless of age or occupational category. The questionnaire used was semi-closed. A total of 154 people were interviewed.Results and discussion. The results showed that 46.8 % of respondents interest in their ancestry has a playful nature; 37.0 % desire through your family history to better understand the history of their country; 33.0 % of respondents are interested in their ancestry in order to better understand the reasons for their behavior (which is a necessary component of self identification); 32.0 % would like to find ancestors, who could be proud of. Nevertheless, in the case of unsolicited information about the life of their ancestors, are ready to make conclusions about his or her own life less than four percent of the respondents.Conclusion. The author believes that the paper put forward the hypothesis that motifs associated with the need to rethink its social role in terms of responsibility for the acts of their ancestors, do not play a significant role in the study of family history is confirmed by the results of the study. In case of detection of unwanted results, mainly protective mechanisms are becoming actual, ensuring the preservation of psychological comfort.